Hypomethylated interferon regulatory factor 8 recruits activating protein-2α to attenuate porcine epidemic diarrhea virus infection in porcine jejunum - Zong, Qiufang; Qu, Huan; Zheng, Xianrui; Wang, Haifei; Wu, Shenglong; Yin, Zongjun; Bao, Wenbin (Frontiers in Immunology, 2023)
Interferon regulatory factor 8 (IRF8) is a key regulator of innate immune receptor signaling that resists pathogen invasion by regulating cell growth and differentiation. Porcine epidemic diarrhea virus (PEDV) targets intestine and damages the mucosal barrier. However, whether IRF8 regulates PEDV replication remains unclear. We revealed that PEDV infection activated IRF8 expression. Moreover, IRF8 deletion drastically promoted PEDV replication and invasion, increasing the virus copies and titers. Hypomethylation enrichment of activating protein (AP)-2α was significantly negatively correlated with high IRF8 expression, and AP-2α directly targeted the IRF8 promoter to regulate PEDV replication. Furthermore, IRF8 overexpression decreased the cellular reactive oxygen species levels and mitochondrial membrane potential and increased the antioxidant enzyme activities to alleviate PEDV-induced oxidative damage. IRF8 overexpression suppressed apoptotic gene expression, thereby inhibiting apoptosis in response to PEDV stimulation. Taken together, this study demonstrates that AP-2α is involved in PEDV-induced epigenetic modification of IRF8 to reduce cell apoptosis and oxidative stress and facilitate host resistance to PEDV in the intestinal epithelium.